2021
DOI: 10.1017/s0144686x21000696
|View full text |Cite
|
Sign up to set email alerts
|

Caring for a person with dementia during the COVID-19 pandemic: a qualitative study with family care-givers

Abstract: The aim of this study was to explore the experience of family care-givers of people with dementia during the COVID-19 pandemic in the Veneto region of Italy to understand how and to what extent the emergency has affected care-givers’ lives and care routines. Twenty adult children of an ill person were interviewed via phone and video call, in adherence with the restrictions against COVID-19. Thematic analysis showed five main themes: the care-giver's experience, the care recipient's experience, relationships wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(37 citation statements)
references
References 51 publications
2
35
0
Order By: Relevance
“…Caregivers in our study reported the increased restrictions put a strain on the unmet needs of the existing care model in Taiwan and created challenges to the reorganization of daily routines and care relationships for family caregivers. These findings have also been reported for FCGs of PLWDs in Italy [16] and Norway [17], who reported COVID-19 restrictions increased caregiver burden due to difficulties in maintaining daily activities, increased emotional stress, and difficulty in reaching for help [16,17].…”
Section: Discussionsupporting
confidence: 74%
“…Caregivers in our study reported the increased restrictions put a strain on the unmet needs of the existing care model in Taiwan and created challenges to the reorganization of daily routines and care relationships for family caregivers. These findings have also been reported for FCGs of PLWDs in Italy [16] and Norway [17], who reported COVID-19 restrictions increased caregiver burden due to difficulties in maintaining daily activities, increased emotional stress, and difficulty in reaching for help [16,17].…”
Section: Discussionsupporting
confidence: 74%
“…The result of social isolation and anxiety along with the possibility of behavioral changes and confusion place persons with dementia at risk of being hospitalized and further exposed to COVID-19 ( Barclay & Rees, 2020 ; Livingston, et al, 2020 ). In addition, families caring for a person with dementia may feel cut off, overwhelmed and anxious, particularly if loved ones are living with complex health conditions and are at greater risk especially if they are aging at home and not in a long-term care facility ( Cipolleetta, et al, 2021 ; Cruz, et al, 2018 ; Hwang, et al, 2021 ; Lombo, et al, 2021 ; Ramos, et al, 2020 ; Tulloch, et al, 2021 ; Werner, et al, 2021 ; Zucca, et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies [18] have pointed out that loneliness increases the emergence of post-traumatic symptomatology and, more importantly, that both 2 of 16 received and perceived social support could be protective factors against psychological distress [19]. Based on these results, many authors [20][21][22][23][24] have proposed strategies to support older people by maintaining social support and reducing loneliness.…”
Section: Introductionmentioning
confidence: 99%